Economic Empowerment of Residents of Al-Hidayah Kalumbuk Padang Orphanage by Utilizing Virgin Coconut Oil Manufacturing Waste into Nata de Coco Beverage Products as Additional Income: Pemberdayaan Ekonomi Warga Panti Asuhan Al-Hidayah Kalumbuk Padang dengan Pemanfaatan Limbah Pembuatan Minyak Kelapa Murni Menjadi Produk Minuman Nata de Coco Sebagai Penghasilan Tambahan - Suryani; Sri Indrayati; Riche Fermayani; Mardhatillah; Rafnelly Rafky (Journal of Community Service and Application of Science, 2024)
The "Al-Hidayah" orphanage, established in Kalumbuk, Padang City, in 1987, by the Al-Hidayah Foundation. The establishment of this orphanage is because in the Kalumbuk area there are many orphans and orphans, who are economically deprived. They struggle with the cost of living and the cost of education. The number of them at the beginning of the establishment was 35 men, and 15 women. Those who live in the orphanage are boys, while women live with their parents, in houses around the orphanage. The current economic situation of the orphanage is still in shortage, because it still depends on government assistance and donations from the community. Meanwhile, orphanage children have potential, especially high school and junior high school students who number 26 people. If directed to fill their free time with activities that can generate additional income, it will help the economy of the orphanage. Previously, the children of this orphanage had been trained, how to make a VCO by the service team chaired by Prof. Dr. Suryani MSi, at their own expense. In the process of making VCO, the waste, which is in the form of coconut water, is wasted. Partners do not have knowledge about the use of coconut water waste into Nata de coco, as well as used as food and beverages that can be sold and make money. The purpose of the service is to utilize the waste produced by VCO, namely coconut water into Nata de coco and its drinks, to improve the economy of the orphanage. This service program is carried out through training in making Nata de Coco from coconut water and making drinks from Nata de Coco. As a result, Mitra has marketed its products, by serving orders for the procurement of drinks from Nata de Coco at the Wedding Party. So that it has generated an average monthly income of Rp. 6,750,000. This program has succeeded in increasing Partners' income